PEMBELAJARAN IPS BERBASIS SAINS, TEKNOLOGI DAN MASYARAKAT (STM) - Muhammad Nur; Rozayani Rozayani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Social studies education has a role to develop students' abilities so that they can use their reasoning in deciding every problem they face. The low quality of social studies learning and various student problems as part of the community in their environment encourage innovative efforts from social science teachers to optimize learning, especially discussions about the relationship between humans and their environment. Social studies teachers try to help students in solving the problems they face while trying to improve the quality of learning. The goal is to make it easier for students to understand social studies material and get applicable solutions to various problems in their social environment. This article attempts to describe the results of the literature review, the results of observations and the reality of social studies learning. The ideas presented for the problems in this study are Science, Technology and Society (STM)-based social studies learning. This alternative is expected to be solutional and applicable to the social problems of junior high school and madrasah tsanawiyah students.